Pengaruh Customer Relationship Management (CRM) dan Digital Marketing terhadap Customer Loyalty di Kopi Kenangan Garut - Hilman Rismanto; Ghina Saqinah; Trifani Deska Ayu Lestari; Astrit Nurul Fazrin; Nur Afni Hasna Anisya (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study aims to analyze the influence of Customer Relationship Management (CRM) and Digital Marketing on Customer Loyalty among customers of Kopi Kenangan in Garut. The background of this research lies in the high consumption of coffee, particularly among students, which indicates strong potential for building customer loyalty. However, intense competition among coffee brands makes customers easily switch, highlighting the need for effective strategies to retain them. This research employed a quantitative method by distributing questionnaires to consumers of Kopi Kenangan in Garut. The analytical techniques used included descriptive analysis and multiple linear regression to examine the influence of each variable. The results show that both CRM and Digital Marketing have a positive and significant effect on Customer Loyalty. These findings demonstrate that well-managed customer relationships and effective digital marketing efforts can strengthen consumer loyalty in the coffee-based beverage industry.